REGRESSION ANALYSIS OF NUMERIC LITERACY ABILITY TOWARDS STUDENTS' LEARNING OUTCOMES AT SMAN 6 PADANG - Sakti Pratama Yuda; Khairul Azmi; Widdya Rahmalina (UIN Imam Bonjol Padang, 2025)
This research is motivated by the importance of the impact of numeracy literacy skills on learning outcomes. In this literacy and numeracy skills are the basis that must be mastered by students as a reference for basic knowledge to know the next learning or material. This study aims to determine the influence of numeracy literacy on mathematics learning outcomes at SMAN 6 Padang. This study uses a quantitative research type using an ex post facto approach. The object of this research is class XII IPS. Data collection techniques use tests. In the research that the author did, there was no treatment like an experiment but rather what it was. This method uses a hypothesis test, namely to find out how much influence the independent variable has on the dependent variable which is carried out using simple linear regression analysis. The data analysis technique uses a paired sample t-test, which consists of the Shapiro Wilk normality test and the Linearity test. Based on the results of the study, analysis and discussion obtained from the one-sample normality test obtained a significance value of 0.076 0.05 while in the linearity test obtained a significance value (sig 2-tailed) of 0.575 0.05 which means that the data is normally distributed and there is a linear relationship. While in the paired sample t-test obtained a significance (sig. 2-tailed) of 0.027 0.05. In the results of the simple regression analysis Y = 50.713 + 0.249X. This means that the constant of 50.713 means that the consistent value of the learning outcome variable is 50.713. The regression coefficient X of 0.249 states that for every additional one unit of numeracy literacy ability value, there is an effect on learning outcomes of 0.249. The regression coefficient is positive so that it can be said that the direction of the influence of variable X on Y is positive. Based on the table above, it can be seen that 31 respondents produced a correlation value of 0.249. therefore, there is an influence of numeracy literacy on mathematics learning outcomes of SMAN 6 Padang.